A year in the life of GW 170817: the rise and fall of a structured jet from a binary neutron star merger. Issue 2 (13th August 2019) - Troja, E; van Eerten, H; Ryan, G; Ricci, R; Burgess, J M; Wieringa, M H; Piro, L; Cenko, S B; Sakamoto, T
ABSTRACT: We present the results of our year-long afterglow monitoring of GW 170817, the first binary neutron star merger detected by Advanced Laser Interferometer Gravitational-Wave Observatory (LIGO) and Advanced Virgo. New observations with the Australian Telescope Compact Array and the Chandra X-ray Telescope were used to constrain its late-time behaviour. The broad-band emission, from radio to X-rays, is well-described by a simple power-law spectrum with index β ∼ 0.585 at all epochs. After an initial shallow rise ∝ t 0.9, the afterglow displayed a smooth turnover, reaching a peak X-ray luminosity of L X ≈ 5 × 10 39 erg s −1 at 160 d, and has now entered a phase of rapid decline, approximately ∝ t −2 . The latest temporal trend challenges most models of choked jet/cocoon systems, and is instead consistent with the emergence of a relativistic structured jet seen at an angle of ≈22° from its axis. Within such model, the properties of the explosion (such as its blast wave energy E K ≈ 2 × 10 50 erg, jet width θc ≈ 4°, and ambient density n ≈ 3 × 10 −3 cm −3 ) fit well within the range of properties of cosmological short gamma-ray bursts.